1988
DOI: 10.1177/028418518802900514
|View full text |Cite
|
Sign up to set email alerts
|

Lesion of the Anterior Cruciate Ligament and Sagittal Disalignment of the Knee in Weight-Bearing

Abstract: Twenty-nine patients with late reconstructive surgery for anterior cruciate ligament lesions had a clinical and radiologic followup ten years after injury. Anterior sagittal displacement of the tibia was recorded on the routine standing radiographs in 16 knees all having a normal femoro-tibial alignment in the nonweight-bearing position. Five of eleven patients with sagittal displacement of between 10 and 19 mm had early osteoarthrosis, which was confirmed by magnetic resonance imaging in four cases; their age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a comparison of patients undergoing revision and primary ACLR, Won et al [ 99 ] demonstrated that patients undergoing revision ACLR had more frequent varus malalignment and this was associated with a greater tendency for higher-grade radiographic OA at the medial tibiofemoral joint. Sagittal displacement of the tibia was evaluated by Egund and Friden [ 100 ], who reported in a cohort study of 29 patients that 5 of the 11 patients with sagittal displacement of between 10 and 19 mm had developed early OA at 10 years after surgery despite age ranges from 23 to 28 years old. The occurrence of malalignment as a consequence of ACL injury is seen in the report by Dejour et al [ 101 ] which demonstrated that the development of varus deformity, characterizing progressive OA, has its origination in the wear of the posteromedial tibial plateau due to ACL laxity.…”
Section: Demographic Risk Factorsmentioning
confidence: 99%
“…In a comparison of patients undergoing revision and primary ACLR, Won et al [ 99 ] demonstrated that patients undergoing revision ACLR had more frequent varus malalignment and this was associated with a greater tendency for higher-grade radiographic OA at the medial tibiofemoral joint. Sagittal displacement of the tibia was evaluated by Egund and Friden [ 100 ], who reported in a cohort study of 29 patients that 5 of the 11 patients with sagittal displacement of between 10 and 19 mm had developed early OA at 10 years after surgery despite age ranges from 23 to 28 years old. The occurrence of malalignment as a consequence of ACL injury is seen in the report by Dejour et al [ 101 ] which demonstrated that the development of varus deformity, characterizing progressive OA, has its origination in the wear of the posteromedial tibial plateau due to ACL laxity.…”
Section: Demographic Risk Factorsmentioning
confidence: 99%
“…Many studies showed that the conservative treatment of ACL ruptures resulted in a significant increase in osteoarthritis [13,14,33-37]. This prevalent view at the time resulted in the assumption that followed during the late 80s and early 90s that ACL reconstruction would be the solution to prevent later osteoarthritis in ACL injured knees [21-25].…”
Section: Review Findingsmentioning
confidence: 99%